Integrating Scratch-assisted Project-based Learning Worksheets to Enhance Students' Mathematical Problem-Solving Skills and Dispositions - Putra, I Komang Adi; Suweken, Gede; Sudiarta, I Gusti Putu (Jurnal Pedagogi dan Pembelajaran, 2024)
The low level of student engagement in mathematics learning is attributed to the current generation of students being digital natives. While mathematics instruction still relies on 20th-century approaches or teacher-centered learning methods. This study aims to develop a Student Worksheet oriented toward a Project-Based Learning (PjBL) model supported by Scratch for teaching the Pythagorean Theorem, designed to enhance students’ problem-solving abilities and mathematical dispositions. The research adopts a design-based research methodology following the Plomp model, which includes three main phases: preliminary research, prototyping, and assessment. The subjects of this study consisted of one lecturer, two teachers, and eighth-grade junior high school students. Research instruments included a validity sheet to assess the Student Worksheet’s validity, a practicality sheet to evaluate its practicality, essay tests, observation sheets, and a mathematical disposition questionnaire to measure the Student Worksheet’s effectiveness. Data were analyzed using descriptive quantitative analysis. The findings indicate that the developed Student Worksheet meets the criteria of being highly valid, as assessed by experts, highly practical based on classroom trials, and moderately effective in improving students’ problem-solving skills and mathematical dispositions. These results demonstrate that integrating the Project-Based Learning model supported by Scratch offers an innovative instructional approach aligned with the characteristics of digital native learners, while also contributing to the advancement of interactive and student-centered mathematics education.